People, Place and Politics: D’Arcy McNickle’s (Re)Valuing of Native American Principles - John L. Purdy (European Journal of American Studies)
Today, societies have intensified their discourse about the concept of “sustainability,” a term that has expanded to consider the viability of political and economic systems once believed to be inevitable and inviolable. Of course this is not the first time we have searched for a deeper understanding of the interaction between humanity and its surroundings. By looking at the literary production of one Native American author, D’Arcy McNickle, who reached maturity in the 1930s—during the Great Depression and the rise of totalitarian governments—this article considers some implications of the author’s vision of the intersections between political power, human rights, and environmental change: the values that drive our decision-making and subsequent actions. By turning to literature, it asks us to listen to the voices of those who may offer alternative ways of understanding what has happened to our world and where we must go to promote its survival.